2018
DOI: 10.3390/cells7110215
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Rab7 Functions in Mammalian Autophagy: Rab7 Knockout Studies

Abstract: Rab7 (or Ypt7 in yeast) is one of the well-characterized members of the Rab family small GTPases, which serve as master regulators of membrane trafficking in eukaryotes. It localizes to late endosomes and lysosomes and has multiple functions in the autophagic pathway as well as in the endocytic pathway. Because Rab7/Ypt7 has previously been shown to regulate the autophagosome-lysosome fusion step in yeast and fruit flies (i.e., autophagosome accumulation has been observed in both Ypt7-knockout [KO] yeast and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 42 publications
0
71
0
Order By: Relevance
“…A recent study demonstrated that ULK1 regulates not only the initiation step but also fusion with lysosome [31]. For further details regarding the molecular basis of autophagosome and autophagolysosome formation, please refer to previous review articles [30,32,33].…”
Section: Mechanism Of Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that ULK1 regulates not only the initiation step but also fusion with lysosome [31]. For further details regarding the molecular basis of autophagosome and autophagolysosome formation, please refer to previous review articles [30,32,33].…”
Section: Mechanism Of Autophagymentioning
confidence: 99%
“…Mechanistically, Sirt1 deacetylates and activates FoxO family transcription factors (Fig. 3), thereby facilitating autophagy through upregulation of Atg genes and Rab7 [74,75,93], a regulator of autophagosome and autophagolysosome maturation [32,33]. Sirt1 localizes in the nucleus, as well as the cytoplasm, and cytosolic Sirt1 can also increase autophagy [91].…”
Section: Sirtuinsmentioning
confidence: 99%
“…Other adaptor proteins selectively promote or inhibit autophagosome transport and autophagosome-lysosome maturation through direct binding to kinesin and dynein [11]. Of these proteins, Rab7 is a vesicular transportrelated protein that promotes the fusion of autophagosomes and lysosomes by regulating their movement on the microtubules [12,13]. Rab7 binds to oxysterol-binding protein-related protein 1L (ORP1L), and then connects to dynein-dynactin [13].…”
Section: Agingmentioning
confidence: 99%
“…Depletion of the RAB7 GAP Armus impairs autolysosome formation and acidification (Carroll et al, 2013). RAB7 knockout cells show accumulation of autolysosomes, indicating that RAB7 is essential for autolysosome maturation (Kuchitsu and Fukuda, 2018). In EPG5-depleted cells or epg-5 mutant animals, GFP::RAB7 forms abnormally enlarged punctate structures .…”
Section: Discussionmentioning
confidence: 99%